Pengaruh Media Sosial dan Gaya Hidup Terhadap Pembelian Impulsif dengan Moderasi BNPL - Afriani, Dina; Wahyuni, Eka Sri; Harpepen, Andi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to examine the effect of social media and lifestyle on impulse buying behavior with Buy Now Pay Later (BNPL) as a moderating variable for students of the Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu. The research method uses a quantitative approach with data collection techniques in the form of questionnaires distributed to 95 respondents selected using the Slovin formula with an error tolerance level of 10%. Data analysis was performed with multiple linear regression and Moderated Regression Analysis (MRA). The results showed that social media has a positive and significant effect on impulse buying behavior (t = 2.214; sig = 0.029). Lifestyle also has a positive and significant effect on impulse buying behavior (t = 9.202; sig = 0.000) with a more dominant influence (β = 0.825). However, BNPL is not proven to moderate the influence of social media on impulse buying behavior (t = 1.346; sig = 0.182) or the influence of lifestyle on impulse buying behavior (t = 0.061; sig = 0.952). This research implies the importance of developing financial literacy and students' critical awareness of the influence of social media and lifestyle in purchasing decisions, as well as the need for responsible marketing strategies from businesses related to BNPL services.